Tuning interactions of surface‐adsorbed species over Fe−Co/K−Al2O3 catalyst by different K contents: selective CO2 hydrogenation to light olefins - Numpilai, Thanapha; Chanlek, Narong; Poo‐Arporn, Yingyot; Cheng, C. K.; Siri‐Nguan, Nuchanart; Sornchamni, Thana; Chareonpanich, Metta; Kongkachuichay, Paisan; Yigit, Nevzat; Rupprechter, Günther; Limtrakul, Jumras; Witoon, Thongthai (Wiley Blackwell, 2020)
Selective CO2 hydrogenation to light olefins over Fe−Co/K−Al2O3 catalysts was enhanced by tuning bonding strengths of adsorbed species by varying the content of the K promotor. Increasing the K/Fe atomic ratio from 0 to 0.5 increased the olefins/paraffins (O/P) ratio by 25.4 times, but then slightly raised upon ascending K/Fe to 2.5. The positive effect of K addition is attributed to the strong interaction of H adsorbed with the catalyst surface caused by the electron donor from K to Fe species. Although the Fe−Co/K−Al2O3 catalyst with K/Fe=2.5 reached the highest O/P ratio of 7.6, the maximum yield of light olefins of 16.4 % was achieved by the catalyst promoted with K/Fe of 0.5. This is explained by the considerable reduction of amount of H2 adsorbed on the catalyst surface with K/Fe=2.5.